Rangkaian Rancang Bangun Alat Pendeteksi Kebakaran berdasarkan Asap dan Suhu pada Dapur Restoran Berbasis Arduino dan Internet of Things - Irsyad Dzikhrullah; Zuly Budiarso (KITA Institute, 2023)
Fire is a disaster that frequently threatens the safety of people and property. High fire risk requires an efficient and responsive detection system to provide early warning. Therefore, this study applies Internet of Things (IoT) technology as an innovative approach to overcome these challenges. The developed fire detection system integrates various key sensor components to achieve accurate results. The MQ-2 sensor is used to detect the presence of smoke or gas that is an early sign of a fire. Until now, flame detectors are used to detect the presence of fire. In addition, the NodeMCU acts as a data processing hub for these sensors and runs complex detection algorithms. By combining these technologies, research has shown that this fire detection system can provide accurate information in real time when a fire breaks out. Its speed of intervention reduces fire losses, helping the public and firefighters to take appropriate precautions and actions. As such, these systems have the potential to save lives and valuable community property